Faktor-Faktor Yang Berhubungan Dengan Kejadian Hiperbilirubinemia Pada Bayi Di Ruang Perinatologi RSUD Kota Tanjungpinang - Marti Suprihatini; Elvi Murniasih; Umi Eliawati (STIKes Ibnu Sina Ajibarang, 2023)
Hyperbilirubinemia is one of the most frequent clinical phenomena in newborns and the most common cause of hospitalization in newborns. In Indonesia, the incidence of hyperbilirubinemia in newborns is 25-50% in neonates. The incidence of hyperbilirubinemia in the Tanjungpinang City Regional Hospital from January 1 2022 to April 30 2023 was 35.6%. This study aims to determine the factors associated with the incidence of hyperbilirubinemia in infants in the Perinatology room at Tanjungpinang City Regional Hospital. The type of research used is a quantitative analytical method using a cross-sectional research design with a retrospective approach. The population of this study was all 202 babies treated in the Perinatology room and the total sample was 72 medical records of babies who had hyperbilirubinemia. The data collection method uses a data checklist sheet from medical records, then the data is analyzed univariately and bivariately with the Chi-square statistical test. This research hopes that nursing services, especially in the perinatology room, will further improve the quality of service, especially in providing comprehensive nursing care for hyperbilirubinemia babies.